Evaluation of Herbal Mouthwashes Containing Zataria Multiflora Boiss, Frankincense and Combination Therapy on Patients with Gingivitis: A Double-Blind, Randomized, Controlled, Clinical Trial: - Khoshbakht, Zoleikha; Khashabi, Ehsan; khodaie, Laleh; Torbati, Mohammad Ali; Lotfipour, Farzaneh; Hamishehkar, Hamed (Galen Medical Journal, 2019)
Background: Dental plaques as adhesive microbial aggregates on tooth surfaces are considered the first stage of tooth decay as well as gingivitis. Accordingly, the effect of different antimicrobial mouthwashes on removing dental plaques and preventing their formation has been evaluated in various studies. This study aimed to evaluate the efficacy of herbal mouthwashes containing hydro-alcoholic extract of Zataria multiflora (ZM), Frankincense (FR), and a combination of both (ZM+FR) and compare it with chlorhexidine (CHX) mouthwash in subjects with gingivitis. Materials and Methods: In this randomized, controlled, clinical trial a total of 140 patients with gingivitis were divided into four groups including CHX (control group), ZM, FR, and ZM+FR groups. Plaque index (PI), gingival index (GI), and gingival bleeding index (GBI) were measured in days 1, 14, and 21. Results: All three herbal types of mouthwash significantly improved plaque, gingivitis, and gingival bleeding throughout days 14 to 21 (P<0.001). There was no difference between herbal mouthwash with CHX groups. CHX mouthwash showed the most side effects (54.3%), while ZM mouthwash showed the least side effects and the highest consumer satisfaction (5.7% and 94%, respectively). Conclusion: All of the herbal mouthwashes can be good candidates for controlling gingivitis. Comparing with CHX mouthwash, herbal mouthwashes have lower side effects and negligible alcohol content. Among the herbal mouthwashes, ZM outperforms FR and FR+ZM due to its lower side effects and higher levels of patients’ satisfaction. [GMJ.2019;8:e1366]